Radiographic examination in the diagnosis of a curious case associating odontoma to agenesis and supernumerary teeth - Freire, Jéssica De Oliveira Alvarenga [UNESP]; Bianco, Giovanna De Souza [UNESP]; Imada, Thais Sumie Nozu; Salzedas, Leda Maria Pescinini [UNESP]; Ikuta, Carla Renata Sanomiya [UNESP] (Faculdade São Leopoldo Mandic, 2021)
Developmental disorders of human dentition may result in various abnormalities according to etiologic agents and the developmental period involved. The size, shape and number of teeth may be affected. Dental abnormalities can occur singly or in multiples in an individual and may or may not be associated with syndromes. Complementary radiographic examinations are valuable for diagnosis, especially in lesions that are asymptomatic and detected only through examination. The present study is intended to report a case of an incidental finding in panoramic radiography of an odontoma, a supernumerary tooth and permanent tooth agenesis in the same non-syndromic individual. According to the literature, the association of hypodontia and hyperdontia (called concomitant hypo-hyperdontia) is most common. The association of hyperdontia and odontoma is uncommon but still reported. However, regarding the association of hypodontia and odontoma no reports were found, as well as the association of the three pathologies.

Os distúrbios de desenvolvimento da dentição humana podem resultar em diferentes anomalias dependendo do agente etiológico e do período do desenvolvimento acometido. O tamanho, a forma e o número dos dentes, dentre outros, podem ser afetados. Podem ocorrer isoladamente ou em conjunto num mesmo indivíduo, bem como estarem ou não associados a síndromes. Os exames radiográficos complementares são valiosos para o diagnóstico, sobretudo quando as lesões são assintomáticas e detectadas incidentalmente no exame. O presente trabalho relata o caso de achado incidental, em radiografia panorâmica, de odontoma, dente supranumerário e agenesia de dente permanente num mesmo indivíduo não sindrômico. Segundo relatos da literatura, a associação de hipodontia e hiperdontia, denominada hipo-hiperdontia concomitante, é a mais comumente encontrada. A associação de hiperdontia e odontoma é incomum, mas ainda é relatada. No entanto, a respeito da associação de hipodontia e odontoma não foram encontrados relatos, bem como da associação das três patologias.
O exame radiográfico no diagnóstico de um caso curioso associando odontoma à agenesia e dente supranumerário
Keywords: Anodontia; Tooth abnormalities; Tooth, supernumerary; Anodontia; Anormalidades dentárias; Dente supranumerário